Analysis Village Financial Management In Peace Village, Binjai District, Langkat Regency - Azfah Citra Andranida; Galih Supraja (Penerbit Jurnal Indonesia, 2025)
This research was conducted in the village of Peace, Binjai District, Langkat Regency. This study aims to determine the success rate of village financial management with the Open Budget Index approach. The research model was carried out with a qualitative descriptive approach. Data collection techniques were carried out by observation, interviews with selected resource persons, and distributing questionnaires. Samples were selected as many as 80 samples. Data analysis was conducted using qualitative analysis with the Open Budget Index approach. The results of this study concluded that the level of success of village financial management that has been carried out by the Peace Village Government of Binjai District Regency with an average score of 62%, which means it is included in the ‘Sufficient’ classification with the ‘Substantial’ category. The practice of the principle of accountability makes the greatest contribution in determining the value of the success of village financial management with a score of 78%, and community participation contributes the least with a score of 52%. The financial management practices carried out by the Peace Village Government are still constrained in carrying out the principles of village financial management, such as budget realisation reports reported to the public are still simple and simple, there is no other information media available besides infographics that strengthen the quality of transparency, and the supervisory function carried out by the community in monitoring village financial management is still low.